2022
DOI: 10.1101/2021.12.30.474613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonself Mutations in the Spike Protein Suggest an Increase in the Antigenicity and a Decrease in the Virulence of the Omicron Variant of SARS-CoV-2

Abstract: Despite extensive worldwide vaccination, the current COVID-19 pandemic caused by SARS-CoV-2 continues. The Omicron variant is a recently emerged variant of concern and is now taking over the Delta variant. To characterize the potential antigenicity of the Omicron variant, we examined the distributions of SARS-CoV-2 nonself mutations (in reference to the human proteome) as 5 amino acid stretches of short constituent sequences (SCSs) in the Omicron and Delta proteomes. The number of nonself SCSs did not differ m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…While this is a positive aspect, a reasonably high rate of transmission could quickly exhaust existing healthcare ability, resulting in more deaths than predicted. Such healthcare stress may also lead to an increase in mortalities that are not linked to COVID‐19 62 . Omicron multiplies 70 times faster in tissues that line airway passages than the earlier Delta variant, potentially facilitating person‐to‐person spread, according to the researchers.…”
Section: Disease Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…While this is a positive aspect, a reasonably high rate of transmission could quickly exhaust existing healthcare ability, resulting in more deaths than predicted. Such healthcare stress may also lead to an increase in mortalities that are not linked to COVID‐19 62 . Omicron multiplies 70 times faster in tissues that line airway passages than the earlier Delta variant, potentially facilitating person‐to‐person spread, according to the researchers.…”
Section: Disease Severitymentioning
confidence: 99%
“…Such healthcare stress may also lead to an increase in mortalities that are not linked to COVID‐19. 62 Omicron multiplies 70 times faster in tissues that line airway passages than the earlier Delta variant, potentially facilitating person‐to‐person spread, according to the researchers. However, Omicron replicates 10 times slower in lung tissues than the original coronavirus, which could contribute to less severe illness.…”
Section: Disease Severitymentioning
confidence: 99%
“…Our first results on the Omicron variant were obtained immediately after the emergence of the variant and were released as of 3 January 2022 [70]. At that time, only preliminary data were presented about this variant in the literature database.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis suggested that COVID-19 only prevention strategy is the most effective strategy and it averted about 10,500 new co-infection cases. Further, [18,19,20,21,22] studied analysis of COVID-19 and comorbidity specifically diabetes mellitus co-infection model with optimal control. The model showed backward bifurcation caused by parameter accounting for susceptibility for Covid-19 and rate of reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that preventive measures such as number of chlorine water tablets, lockdown, social distancing and number of tests played a key role in reducing spread of the disease. COVID-19 and tuberculosis co-dynamics model with optimal control strategies carried out by [30,13,31,22] suggested that COVID-19 prevention, treatment and control of co-infection yields a better outcome in terms in terms of the number of COVID-19 cases prevented at a lower percentage of the total cost of this strategy. Ordinary differential equations constructed by [32,33,34,35] modeled bifurcation and optimal control analysis of HIV/AIDS and COVID-19 co-infection model with numerical simulation.…”
Section: Introductionmentioning
confidence: 99%